We don't play that way, we play this way: Functional Play Behaviours of Children with Autism and Severe Learning Difficulties. (August 2020) - Hancock, Christina L.
Highlights: Play is important for all children, including children with autism and SLD. Research has focused on the deficits in play skills for children with autism. There are gaps in the evidence regarding content and structures of play. Precise categories of functional play are presented. Functional play is far more complex than currently reconised. Abstract: Background: Research on play for children with autism and severe learning difficulties (SLD) has been limited; instead, much of the research focuses on higher levels of play, such as symbolic play. Those studies that present details regarding functional play are focused on examining the extent of the play deficit and limited in depth with respect to the precision of the categories presented. Therefore, the current understanding, the tools available to support, plan and measure play are not sufficiently detailed or focused on children with autism and SLD. Aims: The aim of the research was to analyse the functional play actions and establish precise functional play categories though direct observations of children aged 3–11 diagnosed with a combination of autism and SLD. Methods: Free-play observations of children diagnosed with autism and SLD (N-27) were conducted in a natural play situation across three special schools in England. Outcomes and Results: The results reveal four key areas of functional play: interacting with one object; interacting with two (or more) objects; interacting with self; and interacting with the environment. In addition, seven subcategories were established as additional components related to functional play. Conclusions and implications: The results suggest that functional play for children with autism and SLD is far more complex than currently recognised. Through the depth and detail established, the categories provide greater understanding of the play characteristics and the most detailed account of the functional play characteristics for this group of children. The analysis provides sensitive measurement scales to support accuracy and precision when planning, supporting and measuring small increments of progress in play.